Transcriptome Analysis in Yeast Reveals the Externality of Position Effects. (19th April 2021) - Gui, Qian; Deng, Shuyun; Zhou, ZhenZhen; Cao, Waifang; Zhang, Xin; Shi, Wenjun; Cai, Xiujuan; Jiang, Wenbing; Cui, Zifeng; Hu, Zheng; Chen, Xiaoshu
Abstract: The activity of a gene newly integrated into a chromosome depends on the genomic context of the integration site. This "position effect" has been widely reported, although the other side of the coin, that is, how integration affects the local chromosomal environment, has remained largely unexplored, as have the mechanism and phenotypic consequences of this "externality" of the position effect. Here, we examined the transcriptome profiles of approximately 250 Saccharomyces cerevisiae strains, each with GFP integrated into a different locus of the wild-type strain. We found that in genomic regions enriched in essential genes, GFP expression tended to be lower, and the genes near the integration site tended to show greater expression reduction. Further joint analysis with public genome-wide histone modification profiles indicated that this effect was associated with H3K4me2. More importantly, we found that changes in the expression of neighboring genes, but not GFP expression, significantly altered the cellular growth rate. As a result, genomic loci that showed high GFP expression immediately after integration were associated with growth disadvantages caused by elevated expression of neighboring genes, ultimately leading to a low total yield of GFP in the long run. Our results were consistent with competition for transcriptional resources among neighboring genes and revealed a previously unappreciated facet of position effects. This study highlights the impact of position effects on the fate of exogenous gene integration and has significant implications for biological engineering and the pathology of viral integration into the host genome.